Rings with projective basic right ideals - Tuganbaev, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
It has been proved that if A is a right-distributive ring, algebraic over its center, and whose principal ideals are projective, then A is a left-distributive ring.